Ostkunst - Westkunst. - Becker, Wolfgang; Ludwig, Peter; Uelsberg, Gabriele (Aachen : Ludwig Forum für Internationale Kunst Aachen, 1991)
(Gonzalez), Eduardo Ponjuan ; (Gonzalez), Lazaro Saavedra ; Aguilera, Alejandro ; Albert, Jurij ; Altenbourg, Gerhard ; Andronov, Nikolaj ; Baselitz, Georg ; Beuys, Joseph ; Birkás, Ákos ; Boltanski, Christian ; Bömmels, Peter ; Brüne, Gudrun ; Bruskin, Grisha ; Bulatov, Erik ; Cucurliev, Petko ; Cujkov, Ivan Semjonovic ; Darboven, Hanne ; Dokoupil, Jiri Georg ; Ebersbach, Hartwig ; Edzgveradze, Gia ; Errò ; Esson, Tomas ; Fajbisovic, Semëon Natanovic ; Filipov, Andrej ; Fischl, Eric ; Friedrich, Wolfgang ; Garciandia, Flavio ; Gille, Sighard ; Gorochovskij, Eduard Semjonovic ; Göschel, Eberhard ; Gundlach, Sven ; Guttuso, Renato ; Heisig, Bernhard ; Immendorff, Jörg ; Jankilevskij, Vladimir ; Kabakov, Ilya ; Kalinin, Viktor ; Kantor, Maksim ; Kiefer, Anselm ; Kolar, Jiri ; Kopystianskaya, Svetlana ; Kopystiansky, Igor ; Kozik, Gregor-Torsten ; Lady Pink ; Lanigan-Schmidt, Thomas ; Lorant, Janos ; Lüpertz, Markus ; Mata, Attila ; Mattheuer, Wolfgang ; Medhermeneutica, V/O ; Mironenko, Sergej ; Morley, Malcolm ; Nadler, Istvan ; Nesterova, Natalija ; Olsvang, Anton ; Orlov, Boris K. ; Ovcinnikov, Niklaj ; Pacev, Atanas ; Penck, A.R. ; Pinczehelyi, Sandor ; Poirier, Anne & Patrick ; Polke, Sigmar ; Quintana, Ciro ; Rink, Arno ; Rodriguez Cardenas, Carlos Alberto ; Ruschmeyer, Heike ; Rusev, Svetlin ; Salle, David ; Schönebeck, Eugen ; Sitte, Willi ; Skulme, Dzemma ; Slepysev, Anatolij ; Smy, Wolfgang ; Starzeneckaja, Irina ; Stejnberg, Edvard ; Strawalde ; Tübke, Werner ; Wahorn, Andras ; Warhol, Andy ; Wasse, Ralf-Rainer ; Wesselmann, Tom ; Zacharov, Vadim ; Zilinskaja, Nina Ivanovna ; Zilinskij, Dmitrij ; Zvezdocëtova, Larisa
biografie, bibliografie
Ostkunst - Westkunst, Ludwig Forum für Internationale Kunst Aachen, 29.6.1991 - 22.9.1991
Duits
boek